A review of branched-chain amino acids in lactation diets on sow and litter growth performance. Issue 1 (1st February 2022) - Holen, Julia P; Tokach, Mike D; Woodworth, Jason C; DeRouchey, Joel M; Gebhardt, Jordan T; Titgemeyer, Evan C; Goodband, Robert D
Abstract: Branched-chain amino acids (BCAA) are three essential amino acids (AA) for lactating sows; however, the effects of dietary Leu, Val, and Ile on sow and litter performance within the literature are equivocal. The BCAA are structurally similar and share the first steps of their catabolism pathway where Leu, Val, and Ile are transaminated through BCAA aminotransferase and irreversibly decarboxylated by the branched-chain α-ketoacid dehydrogenase complex. Although these steps are shared among BCAA, Leu is recognized as the primary stimulator due to Leu's greater affinity towards the enzymes compared to Val and Ile. Since the late 1990s, sows are producing larger and heavier litters and generally consume diets with greater concentrations of Leu and crystalline AA, which may create imbalances among dietary BCAA. Research conducted with growing-finishing pigs confirms that high concentrations of Leu can impair BCAA utilization and growth performance. However, the effects of BCAA on lactating sow and litter performance are not as clearly understood. Within mammary tissue, BCAA uptake is greater than milk output of BCAA since Val, Ile, and Leu are catabolized to form non-essential AA, lactose, fatty acids, and other metabolites. Within the mammary gland, BCAA aminotransferase activity is much higher than within skeletal muscle, liver, or small intestine. Thus, competition among the BCAA, namely, between Leu and Val, can significantly inhibit Val uptake within mammary tissue. Therefore, dietary modifications that mitigate BCAA competition may positively influence Val utilization for colostrum and milk synthesis. Little data exist on Ile and Leu requirements for modern lactating sows. Although Val requirements have been extensively researched in the last 25 yr, an ideal Val:Lys has not been consistently established across experiments. Some studies concluded that total Val concentrations above 120% of Lys optimized performance, whereas others determined that increasing SID Val:Lys from 55% to 136% did not improve piglet growth performance. Although increasing dietary Val positively influences fat and protein composition of colostrum and milk, litter growth during lactation is not always positively affected. Given the competition among BCAA for utilization within mammary tissue, research evaluating the Leu and Ile requirement of modern lactating sows is warranted to fully understand the influence and interactions of BCAA on reproductive and litter growth performance.